TGF-β-driven NK Cells plasticity in hepatocellular carcinoma - Reverberi, Valentina; Montali, Anna; Vecchi, Andrea; Rossi, Marzia; Pelagatti, Alessio; Doselli, Sara; Farina, Benedetta; Olivani, Andrea; Economopoulos, Giorgio; Dalla Valle, Raffaele; Laccabue, Diletta; Ferraglia, Francesca; et al. (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality, with limited curative options for advanced disease. Natural Killer (NK) cells are critical innate immune effectors, but their anti-tumor function is severely compromised by the immunosuppressive tumor immune microenvironment (TIME), particularly through transforming growth factor-beta (TGF-β). This study investigates the pivotal role of TGF-β signaling in modulating NK cell phenotypes and functions within the HCC TIME.Methodsto comprehensively assess TGF-β pathway activation and its impact on NK cells, tumor-infiltrating lymphocytes (TILs) and liver-infiltrating lymphocytes (LILs) were isolated from HCC patients undergoing curative resection. Phenotypic and functional analyses were performed, along with functional restoration experiments targeting TGF-β signaling.ResultsTumor-infiltrating NK cells (TINKs) exhibited significant activation of both canonical (SMAD-dependent) and non-canonical (TAK1/p38 MAPK) TGF-β signaling, with a predominance of the non-canonical pathway. This activation was associated with the emergence of an ILC1-like NK subset (CD103+/CD49a+), which was nearly absent in non-tumor liver tissue. These ILC1-like cells maintained strong cytokine production and expressed high levels of inhibitory receptors (PD-1, TIM-3, TIGIT), whereas conventional NK cells (cNKs; CD103−/CD49a−/CD9−) were functionally impaired. Notably, blocking TGF-β receptor binding and SMAD3 activation restored cNK functionality.Discussionour findings suggest that while non-canonical TGF-β signaling drives phenotypic reprogramming and contributes to NK cell dysfunction, canonical SMAD-dependent signaling remains a key therapeutic target for functional restoration. These results highlight the dual role of TGF-β in immune modulation and suggest that targeted pathway inhibition could enhance innate anti-tumor responses, opening new avenues for combination therapies in HCC.